Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kearifan Lokal pada Pembelajaran Tematik - Fajar Isnaini; Nur Fitriyana; Asep Sukenda Egok (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to develop or create thematic Student Worksheets products based on local wisdom. Testing the validity and practicality of the Thematic LKPD products based on local wisdom for class IV SD Negeri Suban Jaya. This type of research is Research and Development with a 4-D development model. The subjects in this study were fourth grade students at SD Negeri Suban Jaya. Data collection techniques using interviews, observation and questionnaires. Based on the results of the validity assessment from language, media, and material experts, it shows that thematic LKPD based on local wisdom obtains an average score of 3.5. From the analysis of the practicality sheets of students and teachers of Thematic LKPD based on local wisdom, a practicality level of 90.8% was obtained. Based on the research results, it can be interpreted that thematic LKPD based on local wisdom is proven to be valid and practical and can be used in learning. Keywords: LKPD, Thematic, Local Wisdom